Kebiri Kimia sebagai Sanksi Tindakan dalam Double Track System - Jamaludin, Ahmad (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
The punishment policy in the form of chemical castration for perpetrators of sexual crimes is a confusing policy when viewed from the perspective of a double-track system. The application of castration sanctions is contrary to the purpose of action sanctions in the double-track system because it does not aim to restore the perpetrators, but rather to provide a deterrent effect and retaliation. So that the chemical castration policy is wrong because it is not in accordance with following the principle of action sanctions in the double-track system. The research method used is normative juridical using primary and secondary data and then analyzed qualitatively. This study aims to find out about the double-track system and to determine the action of chemical castration in the perspective of the double-track system. The results of this study show, First in the double-track system, the criminal system is known in two ways, namely, through legal sanctions and witnesses of action, legal sanctions are oriented towards revenge for their behavior while action sanctions are oriented towards improving the perpetrators so that they can be accepted back in the community. The two sanctions for castration are not included as witnesses for acts in the double-track system, because the basic idea is to improve the perpetrators, while chemical castration is more directed at retaliation. This research can be a reference for criminal law policymakers so that the legal policy does not get out of the basic idea of criminal law itself. Â  Kebijakan pemidanaan berupa sanksi tindakan kebiri kimia bagi palaku kejahatan seksual menjadi kebijakan yang membingungkan jika dilihat dalam perpektif double track system. Penerapan sanksi tindakan kebiri kimia bertolak belakang dengan tujuan dari sanksi tindakan dalam sistem double track system dikarenakan tidak bertujuan memulihkan pelaku, namun lebih kepada pemberian efek jera dan pembalasan. Sehingga kebijakan kebiri kimia menjadi kebijakan yang keliru karena tidak sesuai dengan prinsip sanksi tindakan dalam sistem double track system. Penelitian ini menggunakan yuridis normatif dengan menggunakan data primer dan sekunder kemudian dianalisis secara kualitatif. Penelitian ini bertujuan untuk mengetahui tentang double track system dan untuk mengetahui tindakan kebiri kimia dalam perÂspektif double track system. Hasil penelitian ini menunjukan, Pertama dalam sistem double track system, sistem pemidanaan dikenal dengan dua jalan yakni melalui sanksi hukum dan saksi tindakan, sanksi hukum berorientasi pada upaya balas dendam terhadap prilakunya sedangkan sanksi tindakan berorientasi pada perbaikan pelaku agar bisa diterima kembali di masyarakat. Kedua saknsi tindakan kebiri tidak termaÂsuk saksi tindakan dalam double track system, sebab ide dasarnya perbaikan terhadap pelaku sedangkan kebiri kimia lebih mengarah kepada pembalasan. Penelitian ini dapat menjadi referensi pembuat kebijakan hukum pidana agar kebijakan hukum tersebut tidak keluar dari ide dasarnya hukum pidana itu sendiri.